Post-Retirement Social Adjustment Problems among Male Senior Citizens in Urban Punjab, Pakistan: A Phenomenological Analysis - Beenish Ijaz Butt; Uzma Ashiq; Arjumand Mansoor (ASIAN Journal of International Peace & Security (AJIPS), 2021)
Old age is characterized by different changes in an individual’s life, and one of those remarkable events is termed as ‘retirement’. After retirement starts a transitional phase for the aged people. At the age of 59 years, 11 months, and 29 days, an individual is at a job; on the next day, he/she is a retiree. This article aims to describe the mode of various problems in social adjustment among male senior citizens after retirement in Punjab. The present research conducted the interviews with the retired male senior citizens in urban areas of Punjab by using an interview guide and collected data. It followed multi-stage sampling and included three steps i.e. firstly, three districts of Punjab were selected randomly; secondly, pension pay-centers were chosen purposively. It had the participants who were retired male senior citizens from the formal labor force and aged between 61-63 years only. Significant themes generated out of saturated data were “I am no more employed: Problems of Retired Male Senior Citizens, Post-retirement social adjustment difficulties and Factors responsible for social adjustment of retired male senior citizens.” It was concluded that the government lacks future planning and consequently retirees face problems in social adjustment according to the new patterns of their life. It is recommended that the government pay attention to the better adjustment of retired senior citizens by establishing unique recreational spots by utilizing existing public institution buildings.